Pengaruh Kompetensi Manajerial Kepala Sekolah dan Budaya Kerja Terhadap Disiplin Guru di SD Islam Al-Ikhlas Cipete Jakarta Selatan - Lia Riyani (Bidayatuna, 2020)
This study aims to determine and examine empirical data related to the influence of principals' managerial competencies and work culture on teacher discipline separately or simultaneously. In this study, the authors used a survey method with a correlational and regression approach to the quantitative data obtained from the object of research, namely teachers at SD Islam Al-Ikhlas Cipete South Jakarta. The sample of this study was 66 respondents from 66 populations. The data collection is done by using questionnaire / questionnaire techniques, observation, and documentation. The type of analysis used is the regression analysis which is described descriptively. The results of this study are: 1) There is a positive relationship, which is quite strong and significant between principals' managerial competencies and teacher discipline, which is shown by a simple correlation coefficient (ry.1) is 0.408 (the correlation is quite strong) and the determination coefficient (R2) = 0.166, which means that Principal's managerial competence contributes to teacher discipline by 16.6% and the remaining 84.4% is determined by other factors. 2) There is a positive relationship, quite strong and significant between work culture and teacher discipline, which is shown by a simple correlation coefficient (ry.2) is 0.321 (the correlation is quite strong) and the determination coefficient (R2) = 0.103, which means that work culture provides contribution to teacher discipline is 10.3% and the remaining 89.7% is determined by other factors. 3) There is a positive, strong and significant relationship between principals' managerial competencies and work culture together with teacher discipline, which is indicated by multiple correlation coefficients (Ry. 1.2) is 0.470 (quite strong correlation) and coefficient of determination (R2) = 0.221, which means that principals' managerial competencies and work culture together contribute to teacher discipline by 22.1% and the rest 77.9% is determined by other factors.